2022
DOI: 10.1159/000526653
|View full text |Cite
|
Sign up to set email alerts
|

The Infected Lungs and Brain Interface in COVID-19: The Impact on Cognitive Function

Abstract: Many coronavirus disease 2019 (COVID-19)-recovered patients report signs and symptoms and are experiencing neurological, psychiatric, and cognitive problems. However, the exact prevalence and outcome of cognitive sequelae is unclear. Even though the severe acute respiratory syndrome coronavirus 2 has target brain cells through binding to angiotensin-converting enzyme 2 (ACE2) receptor in acute infection, several studies indicate the absence of the virus in the brain of many COVID-19 patients who developed neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Compared to aging, chronic diseases (e.g., IBD and silicosis) are characterized by significantly different peripheral immune profiles, such as increased IL1β + DCs and monocytes, enrichment of γδ T-cell subsets, and up-regulated expression of HLA-DR, a marker of T-cell (CD3 + , CD4 + , and CD8 + ) activation ( Brilland et al, 2019 ; Boland et al, 2020 ; Mitsialis et al, 2020 ). Acute inflammatory stress also differs from chronic peripheral inflammation in the initial phase, the former is often accompanied by short-term exacerbations and intense immune cell activation, aggregation, and inflammatory storm formation, often with highly activated macrophages, neutrophils, and mast cells mediating activation of innate intrinsic immunity, e.g., COVID-19 and surgically-induced aseptic injury ( Joaquim et al, 2022 ; Bhuiyan et al, 2023 ). Some acute inflammatory events can be followed by transformation into chronic inflammatory processes, e.g., long COVID-19, with long-term neurocognitive effects ( Joaquim et al, 2022 ).…”
Section: Mechanisms By Which Peripheral Inflammation Promotes Central...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to aging, chronic diseases (e.g., IBD and silicosis) are characterized by significantly different peripheral immune profiles, such as increased IL1β + DCs and monocytes, enrichment of γδ T-cell subsets, and up-regulated expression of HLA-DR, a marker of T-cell (CD3 + , CD4 + , and CD8 + ) activation ( Brilland et al, 2019 ; Boland et al, 2020 ; Mitsialis et al, 2020 ). Acute inflammatory stress also differs from chronic peripheral inflammation in the initial phase, the former is often accompanied by short-term exacerbations and intense immune cell activation, aggregation, and inflammatory storm formation, often with highly activated macrophages, neutrophils, and mast cells mediating activation of innate intrinsic immunity, e.g., COVID-19 and surgically-induced aseptic injury ( Joaquim et al, 2022 ; Bhuiyan et al, 2023 ). Some acute inflammatory events can be followed by transformation into chronic inflammatory processes, e.g., long COVID-19, with long-term neurocognitive effects ( Joaquim et al, 2022 ).…”
Section: Mechanisms By Which Peripheral Inflammation Promotes Central...mentioning
confidence: 99%
“…Acute inflammatory stress also differs from chronic peripheral inflammation in the initial phase, the former is often accompanied by short-term exacerbations and intense immune cell activation, aggregation, and inflammatory storm formation, often with highly activated macrophages, neutrophils, and mast cells mediating activation of innate intrinsic immunity, e.g., COVID-19 and surgically-induced aseptic injury ( Joaquim et al, 2022 ; Bhuiyan et al, 2023 ). Some acute inflammatory events can be followed by transformation into chronic inflammatory processes, e.g., long COVID-19, with long-term neurocognitive effects ( Joaquim et al, 2022 ). Unlike chronic inflammation, in acute inflammation, after the pathogen is removed or stress is blocked, damaged tissue is healed and the body’s inflammatory status and immunity returns to normal.…”
Section: Mechanisms By Which Peripheral Inflammation Promotes Central...mentioning
confidence: 99%
“…The virus causes microvascular changes or damage to lung function resulting in impaired flow of oxygen to the brain with subsequent impaired cognitive function. [43][44][45][46] COVID-19 has an additional risk dimension when it comes to Alzheimer's disease (AD), as COVID-19 has been shown to exacerbate the main pathological components of AD, such as beta-amyloid neurotoxicity and pathological tau accumulation. [47][48][49][50][51] It has also been suggested that COVID-19 might impair amyloid processing and mimic cerebrospinal fluid and serum biomarkers of AD, with decreased amyloid beta loads even in cognitively typical patients.…”
Section: Coronavirus Disease 2019 and The Risk Of Dementiamentioning
confidence: 99%
“…Furthermore, Joaquim and colleagues reviewed neurological manifestations of COVID-19 that included deficits in executive/visuospatial functions (i.e., rapid visual attention, immediate recall, information processing speed), working memory, verbal learning, language, orientation, and abstraction [8]. Interestingly, the authors highlighted how cognitive impairment was not linked only to the acute phase of SARS-CoV-2 infection.…”
mentioning
confidence: 99%